Real-time animation of grass - Chen, Kan (2010)
Real-time grass has many applications, such as in games, simulators and virtual reality. Physically-based simulation of grass-grass, grass-object, grass-terrain and grass-wind interactions requires a high computational cost. In this thesis, we present a method to animate grass in real-time by considering a grass eld as a 2D continuum and shifting the complex interactions to the dynamics of continuum. We adopt a wave simulation as the numerical model for the dynamics of continuum which represents grass-grass interaction. Using the wave simulation, we modify the bending angle and the bending velocity of grass. We propose a procedural approach to handle grass-object and grass-wind interactions which directly updates the bending angle and the bending velocity of the grass that collides with the object and wind. Then, we propagate the bending angle and bending velocity to the neighboring grass using the wave simulation. To avoid the intersection between grass and the terrain, the maximum bending angles are calculated based on the slope of the terrain and the bending direction of the grass. The proposed method can be efficiently implemented on a GPU. As a result, massive amount of grass can interact with moving objects and wind in real-time.